Mark Twain's Pudd'nhead Wilson Race, Conflict and Culture - Robinson, Forrest G. 1940-; Gillman, Susan Kay (Duke University Press, 1990)
This collection seeks to place Pudd'nhead Wilson-a neglected, textually fragmented work of Mark Twain's-in the context of contemporary critical approaches to literary studies. The editors' introduction argues the virtues of using Pudd'nhead Wilson as a teaching text, a case study in many of the issues presently occupying literary criticism: issues of history and the uses of history, of canon formation, of textual problematics, and finally of race, class, and gender.In a variety of ways the essays build arguments out of, not in spite of, the anomalies, inconsistencies, and dead ends in the text itself. Such wrinkles and gaps, the authors find, are the symptoms of an inconclusive, even evasive, but culturally illuminating struggle to confront and resolve difficult questions bearing on race and sex. Such fresh, intellectually enriching perspectives on the novel arise directly from the broad-based interdisciplinary foundations provided by the participating scholars. Drawing on a wide variety of critical methodologies, the essays place the novel in ways that illuminate the world in which it was produced and that further promise to stimulate further study.Contributors. Michael Cowan, James M. Cox, Susan Gillman, Myra Jehlen, Wilson Carey McWilliams, George E. Marcus, Carolyn Porter, Forrest Robinson, Michael Rogin, John Carlos Rowe, John Schaar, Eric Sundquist